2022
DOI: 10.3389/fphar.2022.826771
|View full text |Cite
|
Sign up to set email alerts
|

Co-Delivery of p53 Restored and E7 Targeted Nucleic Acids by Poly (Beta-Amino Ester) Complex Nanoparticles for the Treatment of HPV Related Cervical Lesions

Abstract: The p53 gene has the highest mutation frequency in tumors, and its inactivation can lead to malignant transformation, such as cell cycle arrest and apoptotic inhibition. Persistent high-risk human papillomavirus (HR-HPV) infection is the leading cause of cervical cancer. P53 was inactivated by HPV oncoprotein E6, promoting abnormal cell proliferation and carcinogenesis. To study the treatment of cervical intraepithelial neoplasia (CIN) and cervical cancer by restoring p53 expression and inactivating HPV oncopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Directly targeting E6 and E7 using CRISPR has been shown to be successful in clearing HPV + cervical cancer tumours in vivo [21]. It is likely that combination therapy of targeting HPV oncogenes and increasing p53 bioavailability can result in an additive effect as recently demonstrated by Xiong et al, [22]. Nonetheless, the positive effect of increasing p53 bioavailability in HPV driven cancers is clear and re ects the potent anti-tumour effects of p53.…”
Section: Resultsmentioning
confidence: 98%
“…Directly targeting E6 and E7 using CRISPR has been shown to be successful in clearing HPV + cervical cancer tumours in vivo [21]. It is likely that combination therapy of targeting HPV oncogenes and increasing p53 bioavailability can result in an additive effect as recently demonstrated by Xiong et al, [22]. Nonetheless, the positive effect of increasing p53 bioavailability in HPV driven cancers is clear and re ects the potent anti-tumour effects of p53.…”
Section: Resultsmentioning
confidence: 98%
“…In this regard, an in vivo study revealed that a xenograft HPV positive tumor mice model that was locally injected with liposomes containing a CRISPR-Cas9 knocking-down system for E6/E7 from HPV-18 and -16, recovered the expression of p53 and p21 tumor suppressors, followed by a reduction in tumor growth [ 39 , 40 ]. Additionally, it was recently demonstrated that restoration of p53 expression and inhibition of HPV-16 E7 by CRISPR-Cas9 system delivered in nanoparticles in xenograft mice tumors induces a reduction of tumor growth and it is worth mentioning that such treatment exhibits a low toxicity and high transfection efficiency [ 41 ]. However, the use of CRISPR/Cas vectors specifically targeting E6 or E7 in tumor cells is still limited since such vectors have demonstrated low safety and are restricted to a specific HPV viral type.…”
Section: Discussionmentioning
confidence: 99%
“…However, delivery of the CRISPR/Cas system to malignant tumors for efficient treatment keeps challenging and faces critical obstacles. Wang’s laboratory published the report of hyperbranched poly (β-amino ester) based polyplex nanoparticles involving delivery of CRISPR/Cas9 and sgE7 targeted plasmid and achieved the treatment of HPV infection-associated cervical malignancy ( Xiong et al, 2022 ). Zhang et al utilized dLNPs for the co-delivery of focal adhesion kinase (FAK) siRNA, Cas9 mRNA and sgRNA-PD-L1 (siFAK + CRISPR-LNPs) to enhance >10-fold gene-editing efficacy in tumor tissues.…”
Section: Potent Cancer Treatmentmentioning
confidence: 99%